Evaluating the sensitivity of the bovine BCG challenge model using a prime boost Ad85A vaccine regimen. Issue 5 (29th January 2020) - Biffar, Lucia; Blunt, Laura; Atkins, William; Anderson, Paul; Holder, Tom; Xing, Zhou; Vordermeier, Martin; McShane, Helen; Villarreal-Ramos, Bernardo
Highlights: The BCG challenge model is able to distinguish vaccinated from unvaccinated animals. The BCG challenge model can be used to discover protective biomarkers. Abstract: In the absence of biomarkers of protective immunity, newly developed vaccines against bovine tuberculosis need to be evaluated in virulent Mycobacterium bovis challenge experiments, which require the use of expensive and highly in demand Biological Safety Level 3 (BSL3) animal facilities. The recently developed bovine BCG challenge model offers a cheaper and faster way to test new vaccine candidates and additionally reduces the severity of the challenge compared to virulent M. bovis challenge in line with the remits of the NC3Rs. In this work we sought to establish the sensitivity of the BCG challenge model by testing a prime boost vaccine regimen that previously increased protection over BCG alone against M. bovis challenge. All animals, except the control group, were vaccinated subcutaneously with BCG Danish, and half of those were then boosted with a recombinant adenoviral vector expressing Antigen 85A, Ad85A. All animals were challenged with BCG Tokyo into the prescapular lymph node and the bacterial load within the lymph nodes was established. All vaccinated animals, independent of the vaccination regimen, cleared BCG significantly faster from the lymph node than control animals, suggesting a protective effect. There was however, no difference between the BCG and the BCG-Ad85A regimens. Additionally, we analysed humoral and cellular immune responses taken prior to challenge for possible predictors of protection. Cultured ELISpot identified significantly higher IFN-ɣ responses in protected vaccinated animals, relative to controls, but not in unprotected vaccinated animals. Furthermore, a trend for protected animals to produce more IFN-ɣ by quantitative PCR and intracellular staining was observed. Thus, this model can also be an attractive alternative to M. bovis challenge models for the discovery of protective biomarkers.